KARAKTERISTIK SIFAT KIMIA DAN FISIKA TANAH PADI SAWAH PASCA BANJIR BANDANG DI KECAMATAN SILIMA PUNGGA – PUNGGA KABUPATEN DAIRI - Nani Kitti Sihaloho; Elvin Desi Martauli (JURNAL AGROTEKNOSAINS, 2022)
Rice (Oryza sativa L.) is the main food crop commodity that has a strategic function, namely as a staple food, so that domestic rice production plays a role in food security and self-sufficiency. The Ministry of Agriculture has made various efforts and breakthroughs in the midst of the COVID-19 pandemic on food security, including the acceleration of rice planting, development of swamp land, diversification of local food, strengthening of government rice reserves and community food barns. Dairi Regency is one of the rice producers in North Sumatra Province. However, the productivity of rice plants has decreased in Longkotan Village and Bonkaras Village, Silima Pungga - Pungga District, Dairi Regency, due to the flash flood that caused material and land damage. One form of land damage caused is rice fields that have been covered with mud. Based on data from the Dairi Regency agriculture office, after the flash flood in December 2018 resulted in damage to rice fields in Longkotan Village, which was 112 hectares and Bongkaras Village was approximately 40 hectares. The real impact of banjir bandang in addition to reducing rice fields that can be used by farmers, decreasing soil fertility due to environmental damage to rice fields such as loss of top soil which has chemical and physical properties of soil in the availability of nutrients so that it directly causes a decrease in soil productivity and rice plants. Therefore, it is studied to overcome the limited supply of national food, especially rice, through increasing the productivity of paddy fields, especially the chemical and physical characteristics of lowland rice soil after the flash flood so that it can analyze its management efforts to support rice demand in Dairi Regency. The study was to determine the chemical and physical characteristics of the soil of paddy fields after banjir bandang and its management techniques. The research was carried out from April to August 2021 in Longkotan Village and Bonkaras Village. Soil testing was carried out at the Research and Development Center Laboratory of PT. Nusa Pusaka Kencana Analytical & Qc. Laboratory of Bailang High Cliff Gardens, North Sumatra. Soil laboratory tests were conducted to determine the chemical and physical characteristics of the soil. Data analysis was carried out using a descriptive method, namely explaining a situation in the field based on the characteristics of the paddy field soil after the flash flood in the affected village. The results of this study are the clay content and organic matter contained in the soil of the Land Not Affected by Flash Floods. However, the soil pH in the Land Affected by Flash Floods is lower, this is due to the high sand fraction. Soil pH in Land Not Affected by Flash Floods is higher than soil pH in Land Affected by Flash Floods due to the higher organic matter content in Land Not Affected by Flash Floods. Based on the results of the research that the soil that has lower organic C is on the Land Affected by Flash Floods, namely 1.70% which includes low criteria. This is due to the loss of the top soil layer due to flash floods along with the Nitrogen and C-Organic content of the soil in the top soil layer. Because the rate of weathering and Ultisol formation runs faster, the wet climate with high temperature and rainfall causes Ultisols to be poor in organic matter.